2022
DOI: 10.3389/fphys.2022.892623
|View full text |Cite
|
Sign up to set email alerts
|

New permanent bundle-branch block and long-term prognosis of patients with new onset ST-elevation myocardial infarction who underwent percutaneous coronary intervention

Abstract: Aim: The aim of the study was to evaluate the potential predictive value of permanent RBBB and LBBB for longer-term prognosis in patients with new-onset STEMI who underwent percutaneous coronary intervention (PCI).Methods: Patients with new-onset STEMI that underwent emergency PCI at our department from June 2012 to September 2020 were included in the study. Gensini score (GS) was employed to evaluate the severity of coronary lesions. The primary endpoint of the study was the occurrence of major adverse cardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…New-onset RBBB has been included as an early indication of revascularization since 2017 in ESC guidelines for STEMI, thereby highlighting its value in primary revascularization ( 5 ). The prognostic value of new-onset RBBB in AMI has been demonstrated ( 4 , 8 , 20 ). Previous studies even proposed that the mortality of patients with AMI combined with RBBB was higher than that combined with LBBB ( 21 ), especially atypical RBBB ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New-onset RBBB has been included as an early indication of revascularization since 2017 in ESC guidelines for STEMI, thereby highlighting its value in primary revascularization ( 5 ). The prognostic value of new-onset RBBB in AMI has been demonstrated ( 4 , 8 , 20 ). Previous studies even proposed that the mortality of patients with AMI combined with RBBB was higher than that combined with LBBB ( 21 ), especially atypical RBBB ( 7 , 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The previous studies demonstrated that many ECG parameters are associated with the prognosis of AMI (2). New-onset right bundle branch block (RBBB) is a well-recognized ECG marker predicting high mortality (3,4) and an indication of emergency revascularization for AMI patients (5). Owing to the independent blood supply of the right bundle branch (RBB) from the left anterior descending artery (LAD), the incidence of new-onset RBBB in AMI is higher than that of the left branch bundle block (LBBB) (6).…”
Section: Introductionmentioning
confidence: 99%
“…Incidental finding of LBBB in the presence of scar, as shown on cardiac magnetic resonance (CMR) imaging, has worse outcomes than those who have no scar ( 6 ). Bundle branch block (BBB) is deleterious on long-term cardiovascular outcomes and has higher mortality in those individuals with myocardial infarction or abrupt BBB following a percutaneous procedure such as percutaneous coronary intervention (PCI) or transcatheter aortic valve implantation (TAVI) ( 7 ). Meta-analysis of studies shows any form of BBB to have a higher association with mortality in patients presenting with acute heart failure ( 8 ).…”
Section: Conduction Tissue Disease With Bundle Branch Blockmentioning
confidence: 99%